2011
DOI: 10.1016/s2255-4971(15)30235-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis on the Result for Arthroscopic Rotator Cuff Suture Between Smoking and Non-Smoking Patients

Abstract: Objective: To comparatively analyze the results from arthroscopic rotator cuff suture between smoking and non-smoking patients. Methods: A group of 286 patients who underwent arthroscopic suturing of primary rotator cuff injuries between June 12, 2002, and May 14, 2008, was analyzed. The patients included in the study were evaluated using the UCLA scale, with a minimum follow-up of 12 months and average of 56.52 months. The variables studied were age, sex, side operated, dominance, profile of cigarette use and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
2
7
0
1
Order By: Relevance
“…In the present study, among the 18 reoperations, only three (16.6%) were on smokers. Similarly to the data presented by Almeida et al, 20 two had massive lesions and one had a large lesion (cases 1, 5, and 7, respectively). Case 1 reported trauma as a causal factor of the recurrence of symptoms.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the present study, among the 18 reoperations, only three (16.6%) were on smokers. Similarly to the data presented by Almeida et al, 20 two had massive lesions and one had a large lesion (cases 1, 5, and 7, respectively). Case 1 reported trauma as a causal factor of the recurrence of symptoms.…”
Section: Discussionsupporting
confidence: 85%
“…The influence of co-morbidities as indirect causes of healing impairment has been studied. Almeida et al 20 analyzed the relationship between smoking and failed arthroscopic suture in patients operated for RCI and reported that smokers have worse outcomes when compared to non-smokers, but only in case of large and massive lesions. In the present study, among the 18 reoperations, only three (16.6%) were on smokers.…”
Section: Discussionmentioning
confidence: 99%
“…In the period evaluated, 712 original articles were published in the Brazilian Journal of Orthopedics and 588 in Acta Ortopédica Brasileira, or 1300 publications. Among these, 84 (6.7% of the total) were clinical articles on shoulder diseases; 25 publications (1.9% of the total) 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 evaluated the clinical results of treatment of rotator cuff tears ( Table 1 ); twenty studies (80%) were case series (level of evidence IV), one (4%) case–control study (level of evidence III) and four (16%) cohorts (level of evidence II). No randomized study was published in the period.…”
Section: Resultsmentioning
confidence: 99%
“…However, most authors have shown that smoking has a deleterious effect on these patients’ microvascularization, healing and final clinical results. 7 , 8 , 9 , 10 , 36 , 37 In accordance with the trend among the majority of articles in the literature, we excluded smokers.…”
Section: Discussionmentioning
confidence: 99%
“…The patient's age at the time of the surgical procedure seems to have an influence on healing and on gains relating to range of motion and muscle strength. 3 , 4 Other variables such as sex, 5 smoking, 6 , 7 , 8 , 9 , 10 tendon quality shown on magnetic resonance imaging, 11 humerus-acromion distance <7 mm shown on X-rays 12 and impairment of the long head of the biceps have been considered to be deleterious for the final result from the treatment. 13 , 14 , 15 , 16 , 17 …”
Section: Introductionmentioning
confidence: 99%